The - edited by Barbara Thomlison and Kevin Corcoran
The Evidence-Based Internship is a unique teaching and learning tool that combines an internship manual with a text on evidence-based practice. Designed for students entering their field placements in social work and criminal justice-which often overlap-it is built on the premise that students, agencies, and field instructors should be able to provide clients with the best, evidenced-based practice methods currently available. Giving students the confidence to begin their field assignment, it is filled with useful strategies for successfully navigating the internship and honing the skills necessary to become accountable practitioners